Teacher! Please Light My Way: Effect of Providing Individual Feedback on Achievement in Social Studies Education - Akpinar, Mehmet; Özalp, M. Talha (Australian International Academic Centre, 2023)
Feedback in education is messages that contain information about how close the student’s current behavior in the learning process is to the expected behavior, what deficiencies and mistakes exist, and how they can be eliminated, and messages that contain information about the last level reached. Feedback guides students’ learning and is an important component of assessment. In this study, the type of individual feedback was discussed. The research aims to determine the effect of the individual feedback provided to the students from the social studies course on their exam success. The research was conducted with three different social studies teachers and their six different students at three different socio-economic levels. After the teachers were given effective feedback training, two students in their classes were asked to give individual feedback on their lessons. At the end of the process, the exam scores of the students before receiving feedback and the exam scores after receiving feedback were compared according to the class averages. In addition, the opinions of the teachers in this process were also taken in the research. As a result of the research, it was determined that the exam scores of the students who received individual feedback increased and there was a higher change in their scores compared to the class average. According to the teachers, individual feedback increased the students’ interest in the lesson. Finally, teachers suggested to their colleagues that they should receive training on feedback and emphasized that every teacher should be good feedback literacy. Based on these results of the study, it is suggested that teachers should be trained about feedback and that their feedback literacy levels should be increased.
Keywords: 4. Education